(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
The leaf extract of Strobilanthes flaccidifolius Nees. was used for the synthesis of silver nanoparticles through a green technique of synthesis. The nanoparticles was characterized by UV-VIS spectroscopy which proves the formation silver nanoparticles. FTIR (Fourier Transmission infra red spectroscopy) study was carried out to assess the biomolecule as indigo precursors, Energy dispersion X-ray analysis(EDX) data further proves it. EPR (Electron paramagnetic resonance technique) shows the free radical in silver neutral state and XRD(X-ray diffraction technique) also repots silver neutral formation.The morphology and the shape of the silver nanoparticles were determined by Scanning electron microscopy(SEM) and Tunneling electron microscopy (TEM).The nanoparticles adopted spherical morphology and the size ranging from 6nm to 54.11nm and average size was determined as 12.15Â± 5.3nm.The nanoparticles had antimicrobial activity